KAJIAN VISUAL ILUMINASI MOTIF HANJUANG PADA AL-QUR’AN MUSHAF SUNDAWI - Ibrahim, Agus Malik; Ekawardhani, Yully Ambarsih (ARTic, 2022)
This research is motivated by the illumination of the Hanjuang motif on the Sundawi Mushaf Al-Qur'an. Meanwhile, in general, manuscripts that are often circulated in fine print from middle eastern Indonesia use illumination with Islamic geometric patterns. The purpose of this study is to explain the Sundawi Mushaf Al-Qur'an in its entirety related to the formulation of the concept of visualization of Hanjuang motif illumination, explanation of Hanjuang motif illumination, and its influence on Sufism. This study uses descriptive qualitative methods with visual creation approaches and Sufism that systematically describe the things that are the focus of the research. The data collection technique used in this research is library research and field research in the form of document analysis and personal communication with designers, humanists and Sufism experts. The results of this study found that the visualization of Hanjuang motif illumination with Al-Qur'an Mushaf Sundawi is part of plants that exist in West Java and also as a means of introducing West Javanese ornaments in the Sundawi Qur'an. This visual illumination will have an impact on the synergy between the Al-Qur'an Mushaf Sundawi, the Hanjuang motif as part of culture and Sufism. The results of this study refer to the analysis of objects that are concrete or tangible and abstract or conceptual objects that do not refer to objects but the meaning possessed by the illumination object. Keywords: Illumination, Mushaf, Pattern, Hanjuang, Sufism